Correlate of Immune Protection Against HSV-1 Genital Disease in Vaccinated Women - Belshe, Robert B.; Heineman, Thomas C.; Bernstein, David I.; Bellamy, Abbie R.; Ewell, Marian; van der Most, Robbert; Deal, Carolyn D. (The Journal of infectious diseases, 2014)
Background. Previously we conducted a double-blind controlled, randomized efficacy field trial of gD-2 HSV vaccine adjuvanted with ASO4 in 8323 women. Subjects had been previously selected to be seronegative for HSV-1 and HSV-2. We found that vaccine was 82% protective against HSV-1 genital disease, but offered no significant protection against HSV-2 genital disease. Methods. To better understand the results of the efficacy study, post-vaccination anti-gD-2 antibody concentrations from all HSV infected subjects and matched uninfected controls were measured. Three models were used to determine whether these responses correlated with protection against HSV infection or disease. Similarly, cellular immune responses from a subset of subjects and matched controls were evaluated for a correlation with HSV protection. Results. Antibodies to gD-2 correlated with protection against HSV-1 infection with higher antibody concentration associated with higher efficacy. Cellular immune responses to gD-2 did not correlate with protection. Conclusions. The protection against HSV-1 infection observed in the Herpevac Trial for Women was associated with antibodies directed against the vaccine. Clinical Trials Registration. NCT00057330.